The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0100-879x2006005000187
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to gepirone but not to chlordiazepoxide in malnourished rats subjected to learned helplessness

Abstract: The learned helplessness (LH) paradigm is characterized by learning deficits resulting from inescapable events. The aims of the present study were to determine if protein-calorie malnutrition (PCM) alters learning deficits induced by LH and if the neurochemical changes induced by malnutrition alter the reactivity to treatment with GABA-ergic and serotonergic drugs during LH. Well-nourished (W) and PCM Wistar rats (61 days old) were exposed or not to inescapable shocks (IS) and treated with gepirone (GEP, 0.0-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A study conducted in our group showed that rats malnourished in early life presented significant alterations in social interaction behaviors in childhood and these behaviors were related to dominance behaviors in adulthood [45]. During lactation phase the litters were fed diet containing 16% protein (well-nourished) or 6% protein (malnourished).…”
Section: Animal Studiesmentioning
confidence: 99%
“…A study conducted in our group showed that rats malnourished in early life presented significant alterations in social interaction behaviors in childhood and these behaviors were related to dominance behaviors in adulthood [45]. During lactation phase the litters were fed diet containing 16% protein (well-nourished) or 6% protein (malnourished).…”
Section: Animal Studiesmentioning
confidence: 99%
“…A multitude of animal studies have delved into the effects of prenatal PEM during gestation and postnatal PEM on behavioral abnormalities in the adult progeny [92, 110]. The protein malnourished rat pups subjected to prenatal and postnatal PEM exhibit greater nesting period and passive [5] but lesser locomotor and exploratory behavior [111] during the preadolescent period while exhibiting aggressive and dominance behavior traits in adulthood [112]. Prenatal and postnatal PEM is also associated with deficits in spatial learning and memory in adult rats despite allowing nutritional recovery [113].…”
Section: Discussionmentioning
confidence: 99%
“…Considering several prior studies, it is plausible that the behavioral changes observed may be due to morphological, biochemical and/or functional alterations in the Central Nervous System (Almeida et al, 1996a;Bedi, 1991;Cintra et al, 1990;Galler et al, 1995;Huang et al, 2003;Lukoyanov & Andrade, 2000;Matos et al, 2011;Morgane et al, 1993;Morgane et al, 2002;Zhang et al, 2010), specifi cally on stress response regulation (Camargo, Nascimento, & Almeida, 2008;Françolin-Silva & Almeida, 2004;Rocinholi et al, 1997), observed in prenatal (Almeida, Tonkiss, & Galler, 1996b;Almeida, Tonkiss, & Galler, 1996c;Morgane et al, 1993) and postnatal malnutrition (Almeida et al, 1991;Camargo & Almeida, 2005;Castro, Tracy, & Rudy, 1989;Fukuda et al, 2002;Fukuda et al, 2007;Valadares et al, 2010).…”
Section: Discussionmentioning
confidence: 99%